Pengaruh Current Ratio (CR) dan Debt to Total Asset Ratio (DAR) terhadap Pertumbuhan Laba : Studi Empiris Pada Perusahaan Infrastruktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2023 - Mutiara Nudia Anugrah; Rini Idayanti; Hartas Hasbi (AKUNTANSI 45, 2025)
This study aims to analyze the influence of the Current Ratio and Debt to Total Aset Ratio on profit growth in infrastructure sector companies listed on Indonesia Stock Exchange (IDX) during period 2020-2023. The data used is secondary data obtained from financial statements published by the IDX for the years 20202-2023. The sample was selcted using the purposive sampling method, and the number of samples that met the criteria was 31 companies, with a total of 65 observations. This research uses a quantitative method. The research hypotesis was tested using multiple linear regression analysis and path analysis, assisted by the Statistical Package for the Social Sciences (SPSS) version 26. The results show that the Current Ratio has a positive and significant effect on profit growth in infrastructure companies listed on IX during 2020-2023. This is evidenced by the hypotesis testing result showing a coefficient value of 0.15 with a significance level 0.000 (<0.05) . The Debt to Total Asset Ratio also has positive and significant effect on profit growth in infrastructure comapnies listed on IDX during period 2020-2023, with a coefficient value of 0.782 and a significant level 0.000 (<0.05). The Current ratio and Debt to Total Assset Ratio simultaneously have a significant effect on profit growth in infrastructure comapnies listed on the Indonesian Stock Exchange (IDX) for the period 2020-2023.